Effectiveness Of Criminal Enforcement Against Kreak In Juvenile Justice System Semarang Regency - Winarsih, Laras; Ekaningsih, Lailasari; Alid, Idul Hanzah; Izziyana, Wafda Vivid (Fakultas Syariah INSURI Ponorogo, 2026)
This study examines the effectiveness of criminal law enforcement against street children associated with the